Recrystallization behavior of hot-rolled pure tungsten and its alloy plates during high-temperature annealing. (May 2018) - Tsuchida, Kohei; Miyazawa, Takeshi; Hasegawa, Akira; Nogami, Shuhei; Fukuda, Makoto
Highlights: We conducted isothermal and isochronous annealing, electron backscatter diffraction observations and Vickers hardness test. We observed the change of the grain structure and hardness induced by recrystallization. We found the temperature and duration at which recrystallization occurs increase with the dispersion of K bubbles and a solid solution of Re. Abstract: We aimed to clarify the behavior of change in the grain structure and hardness of hot-rolled pure W and its alloys plates developed for various properties by holding at high temperature for long and short durations in the absence of irradiation. The isothermal annealing was performed at 1100 °C for 10–3115 h. The isochronous annealing was performed for 1 h in a temperature range of 1100 to 2300 °C. After heat treatment, the grain structure was observed using electron backscatter diffraction (EBSD) and the Vickers hardness was measured in the observed plane. Pure W did not recrystallize by the heat treatment for a short duration of 1 h at 1100 °C, while the recrystallization of pure W progressed during the heat treatment for long duration of 3115 h at 1100 °C. The temperature and duration at which the recrystallization occurs increase because of the dispersion of K bubbles and solid solution of Re. Considering the actual operation period of fusion reactors, a temperature of 1100 °C can result in recrystallization. It is necessary to decrease the maximum operating temperature or to use materials having a high recrystallization temperature by alloying.